The association between physical activity and sexual dysfunction in patients with diabetes mellitus of European and South Asian origin: The Oxford Sexual Dysfunction Study. Issue 1 (December 2015) - Malavige, Lasantha; Wijesekara, Pabasi; Ranasinghe, Priyanga; Levy, Jonathan
Abstract Background The present study aims to evaluate the relationship between physical activity and sexual dysfunction amongst an ethnic South Asian population living in the United Kingdom and compare the association with that of the native Caucasian population. Methods Twenty-five general practitioner clinics from eight primary care trusts in the United Kingdom collaborated in the Oxford Sexual Dysfunction Study. In each practice, a sample of diabetic and non-diabetic patients of European/Europid and South Asian origin were invited for the study. Erectile dysfunction (ED) was assessed using a five-item version of the International Index of Erectile Function. Premature ejaculation (PE) was diagnosed using the premature ejaculation diagnostic tool. Libido was assessed by asking participants to grade their desire for sexual activity. Physical activity during the past week was assessed using the short version of the International Physical Activity Questionnaire (IPAQ). A binary logistic regression analysis was performed in all adults, Europids and South Asians with 'presence of ED' as the dichotomous dependent variable (0 = ED absent; 1 = ED present) and age, diabetes status, physical activity, ethnicity, current smoking and use of antihypertensive medications as the independent variables. Results Sample size was 510, and mean age was 56.9 ± 9.7 years. There were 63.9 % (n = 326) Europid males in the study population. The prevalence of ED was 64.5 % and it was significantly higher in men with diabetes than in those without diabetes (84.4 vs. 49.0 %, p < 0.001). The overall prevalence of PE was 28.8 %, (with diabetes 32.6 %, without diabetes 25.8 %;p = 0.109). Reduced libido was reported by 26.9 % of study participants (with diabetes 32.8 %, without diabetes 22.0 %;p < 0.01). The median (IQR) total physical activity of the study population was 2373 (3612) MET-min/week. In the IPAQ categorical score, 36.8 % (n = 184/434) males were 'highly active', and 17.8 % (n = 89/434) were 'inactive'. In all adults, age (OR: 1.06), South Asian ethnicity (OR: 1.40), physical inactivity (OR: 1.62) and presence of diabetes (OR: 3.90) all were associated with significantly increased risk of developing ED. A similar result was observed in Europids but not in South Asians. Conclusions Erectile dysfunction was associated with physical inactivity, mainly in Europid males, irrespective of diabetes status. This association was not observed in South Asian males with or without diabetes.